Bibliokonseling Meaning of Life Budaya Dayak Kenyah - Yunistia Prahastini; Nur Hidayah; Blasius Boli Lasan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: This study aims to produce a bibliocounseling guide product containing Dayak Kenyah cultural values to fulfill the meaning of life for high school students. This research and development procedure uses the Borg & Gall model. Based on the results of the assessment of experts and potential users, it has met the criteria of usability, feasibility, accuracy, and attractiveness. The bibliocounseling guide product containing Dayak Kenyah cultural values for fulfilling the meaning of life for high school students can be declared as a product that is suitable for use in bibliocounseling activities. The results showed that students had a low category of pretest results, after being given treatment, there were posttest results that students had achieved a high meaning of life value.Abstrak: Penelitian ini bertujuan untuk menghasilkan produk panduan bibliokonseling bermuatan nilai budaya Dayak Kenyah untuk pemenuhan meaning of life siswa SMA. Prosedur penelitian dan pengembangan ini menggunakan model Borg & Gall. Berdasarkan hasil penilaian para ahli dan calon pengguna telah memenuhi kriteria kegunaan, kelayakan, ketepatan dan kemenarikan. Produk panduan bibliokonseling bermuatan nilai budaya Dayak Kenyah untuk pemenuhan meaning of life siswa SMA dapat dinyatakan sebagai produk yang layak untuk digunakan kegiatan bibliokonseling. Hasil penelitian menunjukkan bahwa siswa memiliki kategori rendah dari hasil pretest, setelah diberikan perlakuan terdapat hasil posttest siswa telah mencapai nilai meaning of life yang tinggi.